Exploring patients’ and healthcare professionals’ experiences of patient-witnessed resuscitation: A qualitative study protocol - Fiori, M.; Endacott, R.; Latour, Jos (Blackwell Publishing Ltd, 2018)
© 2018 John Wiley & Sons Ltd Aim: The aim of this study was to explore the experiences of patients and healthcare professionals regarding patients witnessing resuscitation on another patient in hospital clinical wards. Design: Phenomenological qualitative study. Methods: Participants will be recruited from nine wards in a university hospital in England. Data collection will include two in-depth interviews with patients who witnessed resuscitation: the first interview one week after witnessing resuscitation and the second interview after one month. Individual and focus group interviews with healthcare professionals will be also conducted. Data will be transcribed, managed in NVivo 11 and analysed using phenomenological analysis. The National Health Service, Health Research Authority and University Ethics Committee approved the study (May 2018). The study is funded by Resuscitation Council UK (December 2017) and will be conducted between May 2018–March 2019. Conclusion: While witnessed resuscitation is a major topic of interest in nursing, specific research on the impact of patients who witness resuscitation on fellow patients is limited. This study will use qualitative methodology to inform the evidence base of a clinical problem with limited understanding. The findings of this study will contribute to the framework of witnessed resuscitation and to identifying the barriers and enablers towards a greater support of patients who witness resuscitation in hospital. This new acquired knowledge will be beneficial to the improvement of future nursing care. Impact: The evidence gained from this study can support the development and implementation of guidelines and inform hospital policies to support patients witnessing resuscitation to optimize the quality of nursing care provided.